Легенди про походження скіфів та українські казки - Циміданов, В. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryV. Cimidanov. The Legend of Origin Scythian and Ukrainian TalesThe article deals the famous legend about contest third brothers by the power. In this contest won the younger. The legend is famous in the history of Herodot and other nation of the world. The author think that this legend appear in the mythology of Iranian folks. In eastslavonic literature the legend about third brothers appear between XI and XVII.